An international assessment of the adoption of enhanced recovery after surgery (ERAS (R)) principles across colorectal units in 2019-2020 - Kollaborációs szervezet: ESCP Enhanced Recovery Collaborating Group; Pinkney Thomas; Taylor H.; Tong C.; Schmitz N-D.; Morton D. G.; Pinkney T. D.; Bhangu A.; Blackwell S.; Dardanov D.; Dulskas A.; Ábrahám Szabolcs; et al. (2021)
Aim The Enhanced Recovery After Surgery (ERAS (R)) Society guidelines aim to standardize perioperative care in colorectal surgery via 25 principles. We aimed to assess the variation in uptake of these principles across an international network of colorectal units. Method An online survey was circulated amongst European Society of Coloproctology members in 2019-2020. For each ERAS principle, respondents were asked to score how frequently the principle was implemented in their hospital, from 1 ('rarely') to 4 ('always'). Respondents were also asked to recall whether practice had changed since 2017. Subgroup analyses based on hospital characteristics were conducted. Results Of hospitals approached, 58% responded to the survey (195/335), with 296 individual responses (multiple responses were received from some hospitals). The majority were European (163/195, 83.6%). Overall, respondents indicated they 'most often' or 'always' adhered to most individual ERAS principles (18/25, 72%). Variability in the uptake of principles was reported, with universal uptake of some principles (e.g., prophylactic antibiotics; early mobilization) and inconsistency from 'rarely' to 'always' in others (e.g., no nasogastric intubation; no preoperative fasting and carbohydrate drinks). In alignment with 2018 ERAS guideline updates, adherence to principles for prehabilitation, managing anaemia and postoperative nutrition appears to have increased since 2017. Conclusions Uptake of ERAS principles varied across hospitals, and not all 25 principles were equally adhered to. Whilst some principles exhibited a high level of acceptance, others had a wide variability in uptake indicative of controversy or barriers to uptake. Further research into specific principles is required to improve ERAS implementation.
Keywords: Klinikai orvostan